THE OBJECT-ORIENTED ASPECT OF IRVING’S A TOUR ON THE PRAIRIES - Naruhiko Mikado (Universitas Islam Sumatera Utara (UISU), 2019)
This brief paper has basically two aims. First, it intends to introduce object-oriented ontology (OOO), a branch of contemporary thought which regards everything as an individual “object” of equal standing, as a potentially effective theoretical framework to examine a literary text, especially in order to explore the complexity of interactions between/among both human and nonhuman objects on a horizontal plane. Second, it analyzes how the narrator of A Tour on the Prairies, one of the long-neglected texts of Washington Irving, gradually begins to question the naive human/object binary and broadens his horizons through an encounter with another object. Specifically, I examined a series of the contacts which the narrator makes with buffaloes, and then demonstrated how he, though taking a naïve, human-centered schema in the beginning, gradually attains the liberal perspective through the recognition that the object before him is a being that is ontologically equal with him. I concluded the argument by attesting that the text, albeit in a gentle manner, invited us to see the world and existences in it with a more liberal—i.e. object-oriented—perspective.